Melayani Dunia tanpa Menjadi Duniawi - Maria Patricia Tjasmadi; Immanuel Sukardi; Rinawaty Rinawaty (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2022)
The task of a servant of God is to carry out two divine mandates at once, the spiritual mandate of salvation and the social mandate of development. Based on the initial study, there were many problems faced by God's servants in service, related to economic, emotional, and spiritual formation, which are serious problems faced by the world community as a result of the Covid-19 pandemic. The church as an institution, or God's servants as implementers of the divine mandate, is required to reformulate the service model that is relevant to the pandemic situation, during or after it. This study aims to examine how to serve the world without being "worldly". The method used is a qualitative approach (qualitative research), in which research results are presented in the form of descriptive data processed from data sets (written, oral, and behavioral observa-tions). The big dilemma above has been studied correctly and deeply through a spiritual approach without neglecting physical needs. So that God's servants can be a source of blessings in their field of service.Abstrak.Tugas seorang hamba Tuhan adalah mengemban dua mandat ilahi sekaligus, mandat spiritual penyelamatan dan mandat sosial pembangunan. Berdasarkan kajian awal, ditemui banyak permasalahan yang dihadapi oleh hamba Tuhan dalam pelayanan, terkait ekonomi, emosional, dan spiritual formation, yang merupakan persoalan serius yang dihadapi masyarakat dunia sebagai dampak pandemi Covid-19. Gereja sebagai institusi, atau para hamba Tuhan sebagai pelaksana mandat illahi, dituntut dapat merumuskan kembali model pelayanan yang relevan dengan situasi pandemi, selama atau sesudahnya. Penelitian ini bertujuan untuk mengkaji bagaimana cara melayani dunia tanpa menjadi “duniawi”. Metode yang digunakan adalah pendekatan kualitatif (qualitative research), di mana hasil penelitian disajikan dalam bentuk data deskriptif yang diolah dari himpunan data (tulisan, lisan, serta observasi perilaku). Dilema besar di atas telah dikaji secara benar dan mendalam melalui pendekatan rohani tanpa mengabaikan kebutuhan jasmani. Sehingga para hamba Tuhan dapat menjadi sumber berkat di ladang pelayanannya.